Foreign-language teachers' associations' journey from the Soviet period to the XXI century: the Estonian case. - Meristo, Merilyn; Oder, Tuuli; Velberg, Karola (Paedagogica Historica, 2024)
The Soviet period is described as a highly centralised top-down system where schools and teachers had little to say about managerial topics. Instead, change was initiated by the resolutions and decisions of the Ministry of Education. This article aims to shed light on the establishment of Foreign-Language Subject Councils in Soviet Estonia in the 1960s, how and why they turned into communities of practice (CoPs) and the role that teacher agency played in the Soviet foreign-language landscape. The article also shows how the Soviet top-down controlling subject council transitioned into a bottom-up initiative-rich Foreign-Language Teachers' Association (FLTA) during the collapse of the Soviet Union. The ups and downs of FLTAs as well as the development of teacher professionalism are followed through the period of 30 years of Estonian re-independence. As our study shows, there is evidence that FL teachers voluntarily bonded and socialised outside of the school environment. They had a common denominator that pushed them to collaborate closely – the lack of materials. Furthermore, their activities were driven by teacher agency, as we call it today. Their actions involved so much more than just creating materials. Moreover, their communication could also be perceived as a sense of belonging. These three features (joint interest, agency, sense of belonging) are common to CoPs. Thus, the journey of FLTAs from the 1960s to today has been described and explained, in order to better understand the present situation.